2019
DOI: 10.1177/2280800019826512
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of load transfer process between external fixator and bone model by experimental and finite element methods

Abstract: Introduction: Unilateral external fixators are widely used in orthopedics to stabilize fractured bones and to treat limb deformities. One of the main problems is that it is difficult to detect healing status. In addition, whether load transfer progress between the fixator and bone model are the same under axial, torsional, and bending loads has not been studied. Methods: Therefore the main purpose of this study was to detect the load transfer process between the fixator and a bone model by measuring strains on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 42 publications
(47 reference statements)
1
12
0
Order By: Relevance
“…Similar comprehensive work flow in developing a validated numerical model can also be found in [126] , [127] , [128] . Amaro et al.…”
Section: Experimental and Numerical Biomechanical Tests To Evaluate The Efsmentioning
confidence: 84%
See 1 more Smart Citation
“…Similar comprehensive work flow in developing a validated numerical model can also be found in [126] , [127] , [128] . Amaro et al.…”
Section: Experimental and Numerical Biomechanical Tests To Evaluate The Efsmentioning
confidence: 84%
“…Zhao et al. [128] used the finite element software ANSYS to simulate the behaviour of the bone-EF construct during four stages of fracture healing (or growth states), when subjected to axial, bending and torsional loads. The variation of the material properties as well as the boundary condition of the bones during the four stages of healing was incorporated to the numerical model by separate definitions for each stage.…”
Section: Experimental and Numerical Biomechanical Tests To Evaluate The Efsmentioning
confidence: 99%
“…FE methods additionally permit the fracture geometry, state of healing, and implant type to be rapidly and parametrically varied to evaluate implant deflections under innumerable circumstances of clinical relevance. FE and numerical analyses have frequently been implemented in fracture healing studies to evaluate the effects of implant design (59)(60)(61)(62), implant placement (63)(64)(65), bone-implant load transfer (66)(67)(68), screw placement configurations (62,65,69), fracture geometry (65,(70)(71)(72)(73)(74), and the mechanoregulation of healing (70,(75)(76)(77)(78)(79). Yet to the authors' knowledge, only one prior study has implemented this technique to predict implant deflections (56), and this study was limited to a singular variation of fracturetreatment type.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of experimentally obtained data with numerical analyses allowed measuring local bone damage parameters with accuracy. Stress and strain fields in bone tissue result from the application of experimentally equivalent external loads [ 5 , 6 ], providing that constitutive material laws have been correctly adopted. Avery et al [ 5 ] demonstrated the strengthening effect of a prophylactic internal fixation system, using sheep tibia models, commonly used as a human model, and four different configurations of plates for stabilization.…”
Section: Introductionmentioning
confidence: 99%